Do Information Technologies Improve Teenagers’ Sexual Education? Evidence from a Randomized Evaluation in Colombia - Chong, Alberto; Gonzalez-Navarro, Marco; Karlan, Dean; Valdivia, Martín (Published by Oxford University Press on behalf of the World Bank, 2021)
This study reports results from a randomized evaluation of a mandatory six-month Internet-based sexual education course implemented across public junior high schools in 21 Colombian cities. Six months after finishing the course, the study finds a 0.4 standard deviation improvement in knowledge, a 0.2 standard deviation improvement in attitudes, and a 55 percent increase in the likelihood of redeeming vouchers for condoms as a result of taking the course. The data provide no evidence of spillovers to control classrooms within treatment schools. However, the analysis provides compelling evidence that treatment effects are enhanced when a larger share of a student's friends also takes the course. The low cost of the online course along with the effectiveness the study documents suggests this technology is a viable alternative for improving sexual education in middle-income countries.